Non-volatile Memory Effect in Iron Nanoparticles Dispersed Ferroelectric Liquid Crystal - Marino, Lucia; Scaramuzza, Nicola; Marino, Salvatore (IJRDO-Journal of Applied Science, 2019)
The research on new devices dedicated to the information storage represents a field in which the investments and the efforts of both industry and applied sciences are continuously growing in the last decades. This is due to the fact that the development of modern society is strictly connected with the need to increase the amount of information circulating at the global level. All this, increases the demand for increasingly efficient memory systems, both in terms of execution speed and energy consumption. To meet this demand, some frontier research is proposing various alternative solutions to the traditional silicon-based technology. The study proposed in this article is part of the trend of devices based on nanocomposed materials. In particular, a pronounced memory effect has been observed in a commercial ferroelectric liquid crystal doped with iron nanoparticles using a dielectric spectroscopy technique. The experimental data would lead to the hypothesis that this effect is due to a sort of switch between an initial phase, strongly distorted because the presence of the iron nanoparticles, to a restored smectic-C phase which take place by the application of a bias voltage.